Vital threats to human security in Southern Africa : the regional ramifications of the public health crisis in Zimbabwe - Mtero, Shingirai (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2013)
The southern African region is beset with numerous security concerns: pervasive poverty, deepening inequality, starvation, contamination of essential natural resources, violent crime and state oppression. However, the most vital of the region's security concerns in the 21st century is the spread of infectious disease. The region shoulders a disproportionate amount of the continent's infectious disease burden, with diseases such as HIV/AIDS, tuberculosis and malaria claiming more lives every year than any other factor. The nature of these diseases and their propensity to spread, coupled with inadequate regional public health structures pose a significant threat to regional security and stability. The study asserts that southern Africa's security concerns are most appropriately characterised under the paradigm of Human Security. It further asserts that if such vital threats to human security are not adequately managed they have the ability to permeate across state borders, spelling numerous negative ramifications for the region. To this end, the study details the public health crisis in Zimbabwe and its effects on regional security and stability in southern Africa. An enduring political and economic collapse in Zimbabwe led to the dramatic deterioration of its public health sector, the concomitant mass migration of Zimbabwean nationals across the region presented a unique and complex challenge to the Southern African Development Community (SADC) and its member states. As the premier regional governance institution, SADC has failed to adequately mobilise its structures and member states to respond to the challenges resulting from the public health crisis in Zimbabwe. The study explores the factors accounting for this regional inertia, and asserts that while infectious diseases are at present the most vital of the human security threats, similar threats to human security have the potential to affect the region if SADC fails to recognise and prioritise threats to human security as legitimate regional security concerns.
Keywords: Human security -- Africa, Southern; Communicable diseases -- Africa, Southern; Public health -- Zimbabwe; Poverty -- Africa, Southern